2003
DOI: 10.1037/1072-5245.10.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Type A behavior, components, and outcomes: A study of Canadian employees.

Abstract: This study examined the relationship of global Type A behavior and its components (time pressure and hard-driving competitiveness) with individual and organizational outcomes. Data were collected by means of a structured questionnaire from hospital employees (n = 175) and telecommunication employees (n = 110) in a large Canadian city. Global Type A behavior and its 2 components were significantly related to job stress, health problems, job satisfaction, organizational commitment, and turnover motivation in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
2
16
0
2
Order By: Relevance
“…Should an image violation occur (i.e., her values and goals for her personal health and work–family equilibrium do not fit with her current work situation), she is likely to feel her needs are unmet and decide to search for a new job or stay home with her children (Holtom et al, 2005). Prior research has found that physical health problems (Jamal & Baba, 2003; Wegge, van Dick, Fisher, Wecking, & Moltzen, 2006) and emotional exhaustion (Wegge et al, 2006) positively relate to turnover motivations. Thus, if physical or mental health problems arise, a new mother is likely to question the value or even feasibility of staying in her current job.…”
Section: Health Outcomes and Voluntary Turnovermentioning
confidence: 99%
“…Should an image violation occur (i.e., her values and goals for her personal health and work–family equilibrium do not fit with her current work situation), she is likely to feel her needs are unmet and decide to search for a new job or stay home with her children (Holtom et al, 2005). Prior research has found that physical health problems (Jamal & Baba, 2003; Wegge, van Dick, Fisher, Wecking, & Moltzen, 2006) and emotional exhaustion (Wegge et al, 2006) positively relate to turnover motivations. Thus, if physical or mental health problems arise, a new mother is likely to question the value or even feasibility of staying in her current job.…”
Section: Health Outcomes and Voluntary Turnovermentioning
confidence: 99%
“…A cursory search of organizational research in the last 5 years in hospital settings generated a concerning number of published studies done this way, many by well-known scholars (e.g., Benoit-Barné & Cooren, 2009;Bordia, Jones, Gallois, Callan, & DiFonzo, 2006;Coyle-Shapiro, Kessler, & Purcell, 2004;Doorewaard & Brouns, 2003;Ferres, Connell, & Travaglione, 2005;Goodier & Eisenberg, 2006;Grice, Gallois, Jones, Paulsen, & Callen, 2007;Jamal & Baba, 2003;Kaplan & Patel, 2008;Lewis, 2000;Murray & Peyrefitte, 2007;Rooney, Paulson, Callan, Barbant, Gallois & Jones, 2010). Few pay attention to context.…”
Section: Generalizing To Other Organizational Settingsmentioning
confidence: 99%
“…In relation to the second condition of mediation, the relationships between role clarity and each of the four positive and negative psychological states were assessed separately. Role clarity significantly predicted quality of work life (R 2 Italic type: not significant. Bold type: P < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…For example, specific variables associated with the individual such as global Type A behaviour 2 and psychological distress 3 have been implicated in increasing withdrawal behaviours, as have aspects of the workplace such as stress and work overload, 4 low organisational trust, 5 and work monotony. 6 From a theoretical perspective, when workers are exposed repeatedly to negative or demanding work conditions, allostatic load theory 7 predicts that such prolonged exposure leads to a psychophysiological imbalance that eventually results in chronic health complaints.…”
Section: Psychological Antecedents Of Absenteeism and Turnovermentioning
confidence: 99%